Crecimiento de alevines de Ictalurus Balsanus (pisces:ictaluridae) en condiciones de laboratorio (ING) - Luna-Figueroa, Jorge (2002)
A study was conducted to evaluate the effects of three diets on the growth performance of Ictalurus balsanus fingerlings. Fish fry of sized 39.68 ± 2.0 mm in total length and 411.47 ± 17.0 mg in body weight were stocked at 10 organisms per 80L aquariums. The fish were fed with three different diets: I(31.13% protein, 2.70% lipids, 56,53% carbohydrates), II(39,12%, 3,0%, 35,0%), III(53,57%, 19,37%, 4,17%). The increment in body weight and total length of I. balsanus were greater (P<0.05) with diet III(Daphnia sp., 53,57% protein), than with diet I(31,13% protein) and II(39,12% protein). The highest increments 32,10 mg/day and 0.30 mm/day are related with highest food protein concentration. The specific growth rate for weight and total length was 12,33% and 8,92% higher (P<0.05) with diet III. The survival did not differ (P>0.05) among the fish fed with the different diets. Finally its possible to conclude that living food characteristic and specially the high protein concentration of Daphnia sp. increased the specific growth rates of I.balsanus.